[On "The Methodology of Positive Economics"]: Reply - Rotwein, Eugene (Quarterly Journal of Economics, 1962)
Journal Article On “The Methodology of Positive Economics”: Reply Get access Eugene Rotwein Eugene Rotwein University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 4, December 1962, Pages 666–668, https://doi.org/10.2307/1879556 Published: 01 December 1962